Train to Opportunity: the Effect of Infrastructure on Intergenerational Mobility (2020)
Can transport infrastructure promote intergenerational mobility? This paper estimates the causal impact of the railroad network on intergenerational occupation mobility in nineteenth century England andWales.We create a new dataset of father and son pairs by linking individuals across the 100% censuses of 1851, 1881 and 1911. By geolocating individuals down to the street level, we measure access to the railroad network using the distance to the nearest train station. To address the non-random access to the railroad network, we create a hypothetical railway map based solely on geographic cost consideration. We find that sons who grew up one standard deviation (roughly 5 km) closer to the train station are 6 percentage points more likely to work in a different occupation than their father and 5 percentage points more likely to be upward mobile. Access to the railroad network benefitted families at the top and bottom of the occupational ranking. Through a decomposition exercise, we find that the majority of upward mobility is driven by improvements in local labour opportunities.